Sprawozdanie z Międzynarodowej Konferencji Naukowej pt. Entering into Marriage by Proxy in the Internal Law of the Churches and Other Religious Organizations, Rzym 24-25 maja 2018 r. - Tomkiewicz, Małgorzata (Studia Nauk Teologicznych PAN, 2020)
Nie wymagany